Development and Modeling of Water Tank System using System Identification Method - Mohd Aras, Mohd Shahrieel; Mohd Farriz , Md Basar; Hasim, Norhaslinda; Muhammad Nizam , Kamarudin; Jaafar, Hazriq Izzuan (2013)
This paper presents the development and modeling of Water Tank System (WTS) for temperature control using system identification technique. The WTS consists of the tank with 30 liter water, a stirrer, heater and thermocouple was powered by 240VDC and the system run by LabView software. The stirrer used to stabilize the water temperature that installed on the top cover of the WTS. In this project, a prototype of the WTS will be developed first. The WTS will be tested on an open loop system to obtain measured input-output signals. Input and output signals from the system are recorded and analyzed to infer a model. Then, system identification toolbox in MATLAB will be applied to generate a model of the WTS. The experimental testing of WTS only considered in temperature control. The modeling obtained will be used to design the a suitable controller for temperature control. The most crucial issue is the control system. It is needed for the WTS to perform the desired temperature setting. The objective of this project is to reduce or eliminate the overshoot of system response from temperature setting. The conventional controller PID and Fuzzy Logic Controller (FLC) will be used to control the temperature so that the temperature will maintain its desired temperature. The result shows that FLC is the better performance of system response in term of overshoot and oscillation.